Gerstmann‐Sträussler‐Scheinker Syndrome with Variable Phenotype in a New Kindred with PRNP‐P102L Mutation. (19th September 2013) - Riudavets, Miguel A.; Sraka, María Alejandra; Schultz, Marcelo; Rojas, Estefanía; Martinetto, Horacio; Begué, Christian; de, Inés Noher; Poleggi, Anna; Equestre, Michele; Pocchiari, Maurizio; Sevlever, Gustavo; Taratuto, Ana Lía
Abstract Gerstmann‐Sträussler‐Scheinker syndrome (GSS) is a dominantly inherited disorder belonging to the group of transmissible human spongiform encephalopathies or prion diseases. Several families affected by GSS with patients carrying mutations in the prion protein gene have been described worldwide. We report clinical, genealogical, neuropathology and molecular study results from two members of the first Argentine kindred affected by GSS. Both family members presented a frontotemporal‐like syndrome, one with and the other without ataxia, with different lesions on neuropathology. A Pro to Leu point mutation at codon 102 (P102L) of the prion protein gene was detected in one of the subjects studied. The pathogenic basis of phenotypic variability observed in this family remains unclear, but resembles that observed in other P102L GSS patients from the same family.